O sistema renina-angiotensina e a palatabilidade do sabor salgado em ratos com apetite ao sódio - Zenatti, Aline Aparecida (2020)
The renin-angiotensin system (RAS) belongs to mechanisms that control the search and ingestion of hypertonic NaCl in rats with sodium apetite. Here we investigate whether the antagonism of RAS affects hedonic and aversive orofacial motor responses -parameters of palatability - to the intraoral infusion of 0.3 M NaCl (hNaCl). In addition, the literature suggests that sodium appetite is at least in part a consequence of reduced nociception to hypertonic NaCl. Therefore, we investigated whether captopril, a converting enzyme blocker, inhibits sodium appetite followed by alterations in orofacial responses to intraoral infusão to either 0.3 M NaCl or capsaicin, which activates nociception. Adult rats were depleted of sodium by combined injection of furosemide followed by 24 h removal of ambiente sodium. Losartan (intracerebroventricular, 200 g/l), AT1 angiotensin II receptor antagonist, produced a 50-fold increase in aversive orofacial motor responses to hNaCl, thereby reciprocating the relation of hedonic/aversive responses. Losartan also blocked hNaCl intake of the same animals during the sodium apetite test performed immediately after the orofacial recordings. Captopril (intraperitoneal, 30 mg/kg) inhibited by 80% the hedonic orofacial responses to hNaCl. Immediately thereafter, the animals had an alternate 180-minute access between home cage and recording cage in order to record respectively hNaCl intake and orofacial responses to hNaCl. Animals that received vehicle had reduced hedonic responses to hNaCl from 30 minutes to 180 minutes, matching the captopril group. Their aversive responses remained the same. Captopril had no effect on orofacial responses to capsaicin, but produced a 100-70% inhibition of hNaCl intake until 180 minutes. The results suggest that angiotensin II acts in the brain increasing the palatability of hypertonic sodium during the consummatory phase of sodium appetite.